2009
DOI: 10.2214/ajr.07.3345
|View full text |Cite
|
Sign up to set email alerts
|

A Logistic Regression Model Based on the National Mammography Database Format to Aid Breast Cancer Diagnosis

Abstract: Purpose-To create a breast cancer risk estimation model based on the descriptors of National Mammography Database (NMD) format using logistic regression that can aid in decision-making for early detection of breast cancer. Material and Methods-InstitutionalReview Board waived this HIPAA-compliant retrospective study from requiring informed consent. We created two logistic regression models based on the mammography features and demographic data for 62,219 consecutive cases of mammography records from 48,744 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 38 publications
3
53
0
Order By: Relevance
“…In the past, the breast cancer diagnostic problem has been one of the main application areas of classification problems [19][20][21][22][23]. Many modeling, like statistical methods [10][11][12][13][14] are becoming a very popular alternative in handling breast cancer diagnostic tasks. Over the last few years, many studies have shown that data mining techniques such as Artificial Neural Network [19][20][21] and Support Vector Machine [22,23] achieved better performance than did statistical methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past, the breast cancer diagnostic problem has been one of the main application areas of classification problems [19][20][21][22][23]. Many modeling, like statistical methods [10][11][12][13][14] are becoming a very popular alternative in handling breast cancer diagnostic tasks. Over the last few years, many studies have shown that data mining techniques such as Artificial Neural Network [19][20][21] and Support Vector Machine [22,23] achieved better performance than did statistical methods.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have developed a variety of statistical methods for mammographic diagnosis of breast cancer [10][11][12][13][14]. Rakowski and Clark utilized multiple logistic regression to select significant correlates of screening mammogram and used classification-tree (CHAID) to combine the significant correlates into exclusive and exhaustive subgroups [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, in our experience, the careful selection of terminologies and ontologies that fit the requirements of the radiologists is a key to correlate the results acquired with different techniques, possibly in different hospitals. This should help in creating new models that improve the accuracy of computer-assisted breast cancer diagnosis [50].…”
Section: Lessons Learned From Redesigning a Clinical Processmentioning
confidence: 99%
“…1 Many promising semantic CADx algorithms with good to very good diagnostic performance have been proposed; the statistical techniques employed include artificial neural networks, 2,3 Bayesian networks, [4][5][6] decision trees, 7 and logistic regression. 8,9 However, before it is acceptable to actually apply a semantic CADx algorithm in clinical routine, an external validation of the algorithm's diagnostic performance is mandatory. 10,11 External validation is defined as evaluation of the performance of a classification algorithm on data that were not used to generate the algorithm.…”
Section: Introductionmentioning
confidence: 99%